Psychometric evaluation of the abbreviated math anxiety scale in Russian university students - Malykh, Sergey; Pavlova, Anna; Malykh, Artem; Adamovich, Timofey; Tikhoniyk, Alexey; Ismatullina, Victoria; Kolyasnikov, Pavel; Tikhomirova, Tatiana (Frontiers in Education, 2025)
Math anxiety can hinder learning and deter students from pursuing STEM fields. The Abbreviated Math Anxiety Scale (AMAS) is a short measure of math anxiety, but its use among Russian university students has not been previously evaluated. We assessed the psychometric properties of the AMAS in a sample of 6,337 Russian first-year university students (mean age 18.6 ± 0.96; 64.4% female). Confirmatory factor analysis indicated that a bifactor model—with a general Math Anxiety factor and two specific factors (Learning Math Anxiety and Math Evaluation Anxiety)—fit the data best (CFI = 0.995, RMSEA = 0.048). The AMAS demonstrated good internal consistency (Cronbach’s α = 0.82–0.86; McDonald’s ω = 0.83–0.86) and convergent validity via moderate correlations with trait anxiety (r = 0.35–0.44, p < 0.001). Measurement invariance across gender and academic profile (STEM vs. non-STEM majors) was supported, suggesting that the scale functions equivalently across these groups. Overall, the Russian version of the AMAS exhibits strong psychometric properties in this population and can be confidently used to assess math anxiety among Russian university students.